Preparation and characterization of thermally stable phosphonium organoclays and their use in poly(ethylene terephthalate) nanocomposites. Issue 6 (22nd October 2012) - Abdallah, Wissam; Yilmazer, Ulku
Abstract Purification of montmorillonite rich bentonite followed by surface modification using organic salts was performed. The bentonite was purified by sedimentation and then surface modified by ion exchange using alkyl‐ and aryl‐based phosphonium salts. The thermal stability, morphology, melt flow, and mechanical properties of the poly(ethylene terephthalate) (PET) nanocomposites prepared with these organoclays were studied with and without using a reactive elastomeric compatibilizer. TEM results showed that the alkyl based organoclay exhibited better dispersion and thus, higher tensile strength and elongation at break in the PET/organoclay/elastomer ternary nanocomposites than the aryl‐based organoclay did. The notched Charpy impact strength of PET increased from 2.9 to 4.7 kJ m−2 and 3.4 kJ m−2 for alkyl and aryl phosphonium organoclay‐based ternary nanocomposites, respectively. Upon compounding PET with alkyl and aryl phosphonium organoclays, the onset decomposition temperature of PET increased from 413°C to 420°C and 424°C, respectively. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013